Komunikasi Dwisistem pada Anak dengan Ibu Tunarungu: Sebuah Studi Kasus - Irmayani Putri; Reniwati Reniwati; Bahren Bahren (Universitas Andalas, 2018)
This article describes the form and meaning of the sign language used by a child with a deaf mother. Data provided by referral method which are using tapping techniques. Data analyzed uses a pragmatic method with speech partners and determination of other languages. The results show that the object communicates with his mothers occurs hand gestures and body gestures. In this case, the sign language used is not the standard sign language but a habit that is formed because of the similarity with the subject.